Fatigue Resistance of C30 Structural Steel - Libor Trsko; Otakar Bokuvka; Peter Palcek; Frantisek Novy; Katarina Mikova (Communications - Scientific letters of the University of Zilina, 2018)
In this paper the authors present and discuss results of both fatigue life tests and fatigue crack growth rate tests performed for C30 steel which is used for railway axle manufacturing. The obtained results demonstrate the differences in fatigue strength and fatigue crack growth resistance in two different parts of one railway axle which are subjected to different levels of plastic deformation, namely the axle bolster body and axle body.